Delivering Smart Governance in a Future City: The Case of Glasgow - Leleux, Charles (2018)
In 2013, Glasgow City Council received significant funding to develop innovative smart city applications, including the delivery of new electronic public services and the co-production of governance. This case study examines the processes that underpin the ways in which the ‘Future City Glasgow programme’ delivered ‘smart governance’, in the context of a regenerating post-industrial city. We assess the contribution of smart city technologies and data collection and monitoring processes designed to facilitate citizen engagement and sustainable governance practices. The Future City Glasgow programme ran from 2013‒2015, and included the Open Glasgow project, and ‘Demonstrator Projects’ of: Energy Efficiency; Intelligent Street Lighting; Active Travel; and, Integrated Social Transport. Opportunities arose from these demonstrators for developing co-production and legacy initiatives. The case study provides insight into the ways in which citizens and local communities in Glasgow have been engaged in governance processes. This engagement has taken place via traditional and innovative smart city technologies, and in particular in relation to policy formulation, service design and delivery. It finds that the co-creation of governance is shaped by vested interests, that engagement is fragmented and partial, but at the same time new technologies, social media and shared learning opportunities offer innovative new ways for some citizens to influence local governance.